Extensionality of Spatial Observations in Distributed Systems - Caires, Luís (2019)
We acknowledge the Fundação para a Ciência e Tecnologia PhD Scholarship SFRH/BD/23760/2005 and project IP Sensoria IST-2005-16004. We thank the anonymous reviewers for their comments, and Luís Monteiro and Luca Cardelli for useful remarks.